2021
DOI: 10.1007/s10758-021-09564-9
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of a Lesson Study Model into Distance STEM Education during the COVID-19 Pandemic: Teachers’ Views and Practice

Abstract: This paper investigated the integration of a Lesson Study Model (LSM) into distance STEM education during the COVID-19 pandemic. The study focused on six dimensions: (1) STEM education in distance learning, (2) Lesson Study (LS), (3) lesson planning processes, (4) challenges of lesson planning, (5) evaluation and assessment methods, and (6) strategies, methods, and techniques. The sample consisted of 24 science teachers recruited using criterion sampling, which is a purposive sampling method. A case study, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 63 publications
0
21
1
2
Order By: Relevance
“…Emphasizing that they only try to implement the achievements in their own plans in the normal teaching process, the teachers stated that this model can be applied during additional lesson hours and teachers should be paid during these hours. Similar limitations regarding the lesson study have been expressed in many studies (Aykan & Yıldırım, 2022;Chen, 2017;Lampley et al, 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Emphasizing that they only try to implement the achievements in their own plans in the normal teaching process, the teachers stated that this model can be applied during additional lesson hours and teachers should be paid during these hours. Similar limitations regarding the lesson study have been expressed in many studies (Aykan & Yıldırım, 2022;Chen, 2017;Lampley et al, 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 61%
“…The teachers discovered that they learned to take risks regarding the instructional practices, which they could not do before. Demir et al (2013), Dudley (2013), and Aykan & Yıldırım (2022) found in their studies that the lesson study model encouraged teachers to take more risks than normal times and to step out of their comfort zone. Stating that the application process of the model contributed positively to their perspectives on the teaching process, special education teachers expressed that they interacted with their colleagues that they do not normally do.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Our experimentation was carried out at a high school and the Lesson Plan was modified to include the distance learning needs and the resources, agreeing with the conceptual framework (DAD), which is described in the following section. Many scholars (e.g., Aykan and Yildirim, 2022) investigated the integration of the Lesson Study Model into distance education during the COVID-19 pandemic, focusing on several dimensions: Lesson Study in distance learning, lesson planning processes, challenges of lesson planning, evaluation, and assessment methods, new strategies, methods, and techniques. Huang et al (2021) in their article, "Digital technologies, online learning and lesson study, " show how various technologies could be used to modify and strengthen lesson study.…”
Section: Lesson Studymentioning
confidence: 99%
“…However, in the current situation of the COVID-19 pandemic and considering the economic capabilities of students' parents, wise considerations are needed regarding the decision to increase the student's monthly tuition. Another way can be done through collaboration with the government or with other parties who care about education (Aykan & Yıldırım, 2022;Yu & Jee, 2021).…”
Section: Input Evaluationthe Use Of Information and Communication Tec...mentioning
confidence: 99%